Case Report: virus infection-induced exacerbations of lung injury and fibrosis in children with diffuse alveolar hemorrhage: report of three cases - Wei, Qing; Liu, Jing; Chen, Xun; Li, Chunyan; Nong, Guangmin; Li, Yan (Frontiers in Pediatrics, 2025)
Virus infection is a common cause of lung injury and can result in lung fibrosis in severe cases. Furthermore, it is a significant trigger of disease exacerbation in patients with lung fibrosis. However, nearly all the case reports or case series to date have focused on the adult population rather than the pediatric population. Here, we report three cases of virus infection-induced exacerbations of lung injury and fibrosis in children with diffuse alveolar hemorrhage. To our knowledge, this is one of the first articles to report virus infection-induced lung injury and fibrosis in children.